2001
DOI: 10.1159/000059347
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of chromosomal aberrations involving chromosome 1q31→q53 in a DMBA-induced rat fibrosarcoma cell line: amplification and overexpression of <i>Jak2</i>

Abstract: In a study of DMBA-induced rat fibrosarcomas we repeatedly found deletions and/or amplifications in the long arm of rat chromosome 1 (RNO1). Comparative genome hybridization showed that there was amplification involving RNO1q31→q53 in one of the DMBA-induced rat fibrosarcoma tumors (LB31) and a cell culture derived from it. To identify the amplified genes we physically mapped rat genes implicated in cancer and analyzed them for signs of amplification. The genes were selected based on their locations in compara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…Few studies on the cytogenetic characterization of rat cell lines have been performed, particularly using rat or mouse paint probes. However, there have been some reports addressing rat tumor cell lines indicating RNO1 [3] , [29] , [30] , RNO3 [29] , RNO6 [31] and RNO15 [32] , [33] as recurrent and/or relevant chromosomes related to the tumorigenesis/tumor progression in mammary fibrosarcomas, endometrial adenocarcinomas and lung cancer. Also in our study rearrangements in those chromosomes have been identified, as it is the case of the complex rearrangement involving RNO15 ( Figure 4 ), only detected using the combination of varied cytogenetic tools.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies on the cytogenetic characterization of rat cell lines have been performed, particularly using rat or mouse paint probes. However, there have been some reports addressing rat tumor cell lines indicating RNO1 [3] , [29] , [30] , RNO3 [29] , RNO6 [31] and RNO15 [32] , [33] as recurrent and/or relevant chromosomes related to the tumorigenesis/tumor progression in mammary fibrosarcomas, endometrial adenocarcinomas and lung cancer. Also in our study rearrangements in those chromosomes have been identified, as it is the case of the complex rearrangement involving RNO15 ( Figure 4 ), only detected using the combination of varied cytogenetic tools.…”
Section: Discussionmentioning
confidence: 99%
“…Chemically induced carcinogenesis of the rat mammary gland has been used extensively to investigate breast cancer. In rat models, the carcinogenic compound 7,12-dimethylbenz[a]anthrazene (DMBA) is frequently used to induce tumors, and DMBA-induced rat mammary tumors and sarcomas are useful cancer models [2] , [3] , [4] . Using the evolutionary conservation of gene segments as a guide, animal models, such as the rat, constitute powerful tools to decipher pathways and genes involved in tumorigenesis [4] .…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of AI at the Pten locus in the tumor material was performed by allelotyping using a polymorphic intragenic Pten marker (Sjöling et al 2001) as well as four other markers (D1Rat79, D1Rat81, D1Rat169, and D1Rat300), located close to the Pten gene. Primer pair sequences for these markers were obtained from public databases.…”
Section: Ai Scoring At the Pten Locusmentioning
confidence: 99%
“…However, the few reports addressing this issue indicate the following chromosomes to be relevant for tumor progression in mammary fibrosarcomas, endometrial adenocarcinomas, and lung cancer: RNO1 [Popescu and Greiner, 1999;Walentinsson et al, 2000;Sjoling et al, 2001;Louzada et al, 2012], RNO3 [Popescu and Greiner, 1999;Louzada et al, 2012], RNO6 [Adamovic et al, 2005;Louzada et al, 2012], and RNO15 [Dano et al, 2001;Hamta and Talebbeigy, 2010;Louzada et al, 2012]. The cell line analyzed here, CLS-ACI-1, also presents rearrangements in these chromosomes, detected only due to the combination of the cytogenetic techniques used ( figs.…”
Section: Cytogenetic Analysis and Chromosome Reconstruction Of The CLmentioning
confidence: 86%